Influence of Entrepreneurship Education and Training and Business and Professional Infrastructure on the Entrepreneurial Intentions of Palestinian Entrepreneurs - Mahmoud Tahboub; Chokri Slim (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The impact of Entrepreneurship Education and Training (EET) and Business and Professional Infrastructure (BPI) on entrepreneurial intentions (EI) has garnered considerable attention from scholars for many years. The findings were largely consistent and suggested a positive impact of these factors on entrepreneurial intentions (EI). This quantitative study employed an online survey to collect data from participants using random sampling. Factor analysis and multiple regression analysis were performed on the data. The findings suggest that Palestinian entrepreneurs recognize the significance of Entrepreneurial Education and Training (EET) in enhancing their Entrepreneurial intentions (EI), and that those who have engaged with EET are more inclined to possess robust entrepreneurial intentions. The findings further suggest that access to suitable BPI favorably affects their EI and motivates them to initiate their own businesses. The study's findings provide significant insights for Palestinian policymakers and entrepreneurship stakeholders, as they demonstrate that the implementation of well-structured EET programs and the provision of an advanced BPI correlate with a favorable perception of entrepreneurship. Policymakers should endeavor to foster an educational and socio-economic climate, as well as a regulatory framework, that facilitates Palestinians in initiating, operating, and sustaining their businesses. The study's findings offer critical insights for Palestinian policymakers and entrepreneurship stakeholders in formulating effective EET programs to furnish Palestinians with essential entrepreneurial knowledge and to cultivate an attractive BPI that encourages the decision to pursue entrepreneurship, thereby aiming to transform Palestinian society into an entrepreneurial one.